RECEIVE SIGNAL STRENGTH INDICATOR (RSSI) PADA SWARM ROBOT UNTUK MENENTUKAN JARAK ANTARA ROBOT LEADER DAN ROBOT FOLLOWER - I Made Andik Setiawan; Ocsirendi; Sella Amril; Ariansyah Sapta (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Robot is a set of mechanical devices that are programmed in advance to perform a task either with human supervision or control. Robot development continues to be carried out, one of which is swarm robots. Swarm robots are robots that work together like a collection of insects to do a job. The swarm robot consists of a leader robot and a follower robot that must communicate with each other for positioning. The communication system uses two xbee modules to get the Receive Signal Strength Indicator (RSSI) value in determining the distance between robots so that the follower robot can follow the movement of the leader robot. The method used is to test the communication between xbees and the comparison of the RSSI value to distance. Based on the results of the tests carried out, the results showed that the two xbees communicated well with each other and the RSSI values ​​obtained on the X-axis and Y-axis with the same distance did not change significantly.